Mulheres e extensão universitária: olhares sob a perspectiva de gênero nos cursos de agronomia e engenharia florestal, UFLA - Teixeira, Kreicy Mara (2021)
The University Extension is an extremely important for the challenges that are posed day by day for the University, how to build dialogical relation ships and effect the qualification of students for professional exercise. Producing knowledge and making it accessible, is a great challenge for the university. In the present work, we seek to understand possible contributions that extension experiences bring to professional training of the students of the Agronomy and Forestry Engineering courses Ufla. First, an understanding of how the environments of universities, where knowledge is produced are crossed by power relations that (re) produce inequalities and the segregation of the sexual division of labor. Then, we discussed the dialogical relationship between academic knowledge and popular knowledge. Subsequently, we resumed a brief historical context of the university extension, its definition by the National Forum of Pro-Rectors as well as its guidelines. Then a reflection of the extension as an educational action. Finally, we explain about the curriculum in higher education. For this we use qualitative-quantitative research, and the methods adopted are: documentary research, initial quantitative questionnaire and semi-structured interviews. The information obtained through the questionnaires received statistical treatment of analysis. The qualitative information of the research was submitted to content analysis. As a main resultd of this study we had that there are areas that strengthen and strengthen gender inequalities, and that this reflects both within university and in society. Recarding the extension, most of the students did not make or are part of the university extension, mainly from the initial periods, despite considering experiences of positive extension for vocational training. Finally, we can see what extend is relegated and that lacks incentive, motivation and mor e dissemination as well as understand that while the sexual Division of labor adversity and hindmost obstacle to women’s lives, the further away will be from their rights in the.